2015
DOI: 10.1039/c5cc05526a
|View full text |Cite
|
Sign up to set email alerts
|

Compact and stable SNAP ligand-conjugated quantum dots as a fluorescent probe for single-molecule imaging of dynein motor protein

Abstract: Compact SNAP ligand-conjugated quantum dots (<10 nm) with high colloidal stability over a wide range of pH (5-9) have been synthesized as fluorescent probe for the single-molecule imaging of dynein motor protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The size and monodispersity of aqueous CdSe/CdS QDs were unchanged during >4 months of storage at room temperature (Figure S3). In contrast, our attempts to exchange hydrophobic QDs into water by ligand exchange, in which hydrophobic synthetic ligands are replaced by polar ones, 23,24,30 resulted in QDs with poor colloidal stability that aggregated irreversibly over a matter of days (not shown). Whereas these aqueous QDs are smaller than their polymer-wrapped counterparts, the rapid onset of aggregation makes them unsuitable for many imaging experiments.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The size and monodispersity of aqueous CdSe/CdS QDs were unchanged during >4 months of storage at room temperature (Figure S3). In contrast, our attempts to exchange hydrophobic QDs into water by ligand exchange, in which hydrophobic synthetic ligands are replaced by polar ones, 23,24,30 resulted in QDs with poor colloidal stability that aggregated irreversibly over a matter of days (not shown). Whereas these aqueous QDs are smaller than their polymer-wrapped counterparts, the rapid onset of aggregation makes them unsuitable for many imaging experiments.…”
Section: Resultsmentioning
confidence: 89%
“…Single-particle imaging demands that QD probes have exceptional stability, particularly for long-term tracking or use within live cells. Exchange of native ligands for hydrophilic thiols or other coordinating ligands produces functional QDs with small passivation shells, which is an advantage for many imaging applications. , Our attempts to shrink the QD complex by ligand exchange have been unsuccessful in producing single-molecule probes, and we have found that retention of native ligands within a liposome-like structure is essential for the brightness, chemical stability, and photostability required for single-molecule experiments. Monovalent ligands are rapidly displaced by other ligands, such as the thiols found in the cytosol, and are prone to photo-oxidation under the high photon flux required for single-molecule imaging .…”
Section: Resultsmentioning
confidence: 99%
“…The structural data further suggested that the efficiency of alkyl transfer could be reduced by impairing the substrate binding to SNAP‐tag. Based on this, two BG derivatives, that is, BI lacking the 2‐amino group and 7‐deaza‐benzylguanine (deBG) replacing N7 with C7 (Figure 2b), were chosen as the candidates [42,49,50] . Subsequently these substrates were synthesized as described in the Experimental Section and Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, two BG derivatives, that is, BI lacking the 2-amino group and 7-deaza-benzylguanine (deBG) replacing N7 with C7 (Figure 2b), were chosen as the candidates. [42,49,50] Subsequently these substrates were synthesized as described in the Experimental Section and Supporting Information.…”
Section: Structure-based Design and Synthesis Of Snap-tag Substratesmentioning
confidence: 99%
“…Although existing approaches have added significant understanding of the structure and function of receptors, most involve ensemble measurements that lack the specificity to monitor the dynamics of individual receptor–ligand activity. Single-molecule studies of membrane proteins are limited by intracellular autofluorescence, weak fluorophore emission, membrane protein mobility on the cell surface, and high protein concentrations that are incompatible with single-molecule measurements. One approach to address the challenge of fluorophore brightness is the use of relatively large but photostable labels such as quantum dots, which can be utilized to monitor membrane receptor mobility and, in some circumstances, ligand interactions. , However, these studies are complicated by the relatively large size of functionalized quantum dots, and their potential toxicity limits their practical use in many applications …”
Section: Introductionmentioning
confidence: 99%